The Kurdistan Region of Iraq : Assessing the Economic and Social Impact of the Syrian Conflict and ISIS - World Bank (Washington, DC, 2015)
The Kurdistan region of Iraq is facing an economic and humanitarian crisis as a result of the influx of Syrian refugees which began in 2012 and internally displaced persons (IDPs) in 2014. The region's population increased by 28 percent over a short period, placing strains on the local economy, host community, and access to public services. This book provides national and regional policy makers with a technical assessment of the impact and stabilization costs needed for 2015 associated with the influx of refugees and IDPs. The stabilization cost for 2015 is estimated at US$1.4 billion in additional spending above and beyond the region's budget. This estimate could significantly increase should the crisis persist longer.